Progranulin gene variability and plasma levels in bipolar disorder and schizophrenia. - Daniela Galimberti (Public Library of Science (PLoS), 2012)
Basing on the assumption that frontotemporal lobar degeneration (FTLD), schizophrenia and bipolar disorder (BPD) might share common aetiological mechanisms, we analyzed genetic variation in the FTLD risk gene progranulin (GRN) in a German population of patients with schizophrenia (n = 271) or BPD (n = 237) as compared with 574 age-, gender- and ethnicity-matched controls. Furthermore, we measured plasma progranulin levels in 26 German BPD patients as well as in 61 Italian BPD patients and 29 matched controls.A significantly decreased allelic frequency of the minor versus the wild-type allele was observed for rs2879096 (23.2 versus 34.2%, P<0.001, OR:0.63, 95%CI:0.49-0.80), rs4792938 (30.7 versus 39.7%, P = 0.005, OR: 0.70, 95%CI: 0.55-0.89) and rs5848 (30.3 versus 36.8, P = 0.007, OR: 0.71, 95%CI: 0.56-0.91). Mean±SEM progranulin plasma levels were significantly decreased in BPD patients, either Germans or Italians, as compared with controls (89.69±3.97 and 116.14±5.80 ng/ml, respectively, versus 180.81±18.39 ng/ml P<0.001) and were not correlated with age.In conclusion, GRN variability decreases the risk to develop BPD and schizophrenia, and progranulin plasma levels are significantly lower in BPD patients than in controls. Nevertheless, a larger replication analysis would be needed to confirm these preliminary results.